Externalities and optimal taxation - Helmuth Cremer; Firouz Gahvari; Norbert Ladoux (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper re-examines the optimal tax design problem (income and commodities) in the presence of externalities. The nature of the second-best, and the choice of the tax instruments, are motivated by the informational structure in the economy. The main results are: (i) environmental levies (linear or nonlinear) differ in formula from Pigouvian taxes by the expressions for the optimal tax on private goods; (ii) externalities do not affect commodity tax formulas (linear and nonlinear) for private goods; (iii) externalities do not affect the income tax structure if commodity taxes are nonlinear and affect it if commodity taxes are linear; and (iv) a general income tax plus strictly Pigouvian taxes are sufficient for efficient taxation if individuals of different types have identical marginal rates of substitution (at any given consumption bundle).
Keywords: H21; H23; 330; Optimal taxation; Externalities; Environmental levies; Second-best; Informational structure